Diagnostic testing for interstitial lung disease in common variable immunodeficiency: a systematic review - Bintalib, Heba M.; van de Ven, Annick; Jacob, Joseph; Davidsen, Jesper Rømhild; Fevang, Børre; Hanitsch, Leif G.; Malphettes, Marion; van Montfrans, Joris; Maglione, Paul J.; Milito, Cinzia; Routes, John; Warnatz, Klaus; et al. (Frontiers in Immunology, 2023)
Introduction: Common variable immunodeficiency related interstitial lung disease (CVID-ILD, also referred to as GLILD) is generally considered a manifestation of systemic immune dysregulation occurring in up to 20% of people with CVID. There is a lack of evidence-based guidelines for the diagnosis and management of CVID-ILD. Aim: To systematically review use of diagnostic tests for assessing patients with CVID for possible ILD, and to evaluate their utility and risks. Methods: EMBASE, MEDLINE, PubMed and Cochrane databases were searched. Papers reporting information on the diagnosis of ILD in patients with CVID were included. Results: 58 studies were included. Radiology was the investigation modality most commonly used. HRCT was the most reported test, as abnormal radiology often first raised suspicion of CVID-ILD. Lung biopsy was used in 42 (72%) of studies, and surgical lung biopsy had more conclusive results compared to trans-bronchial biopsy (TBB). Analysis of broncho-alveolar lavage was reported in 24 (41%) studies, primarily to exclude infection. Pulmonary function tests, most commonly gas transfer, were widely used. However, results varied from normal to severely impaired, typically with a restrictive pattern and reduced gas transfer. Conclusion: Consensus diagnostic criteria are urgently required to support accurate assessment and monitoring in CVID-ILD. ESID and the ERS e-GLILDnet CRC have initiated a diagnostic and management guideline through international collaboration.